سورۃ النساء کا موضوعاتی مطالعہ اور معاصر مسائل میں اس سے رہنمائی: Thematic study of Surah al-Nisa; A Guide for contemporary Issues - Rabbani, Muhammad Aslam (Al-Amīr Research Journal for Islamic Studies, 2023)
This scholarly article offers an in-depth exploration of Surah An-Nisa, a pivotal chapter in the Quran that addresses a wide array of social, moral, and legal issues, particularly those pertaining to women and family life. Surah An-Nisa, which translates to "The Women" in English, is the fourth chapter of the Quran and consists of 176 verses. This Surah is notable for its detailed discussion on the rights and responsibilities of individuals within the Islamic community, with a significant emphasis on improving the status of women and protecting the vulnerable. Through a meticulous examination of its verses, the article sheds light on the profound virtues, multifaceted themes, and the enduring relevance of Surah An-Nisa in contemporary society.The article begins by providing a comprehensive introduction to Surah An-Nisa, outlining its historical context and the circumstances surrounding its revelation. It emphasizes the Surah’s unique position in the Quranic canon for its detailed legislative content, which aims at establishing justice, equality, and moral conduct among the believers. Following this introduction, the article transitions into a discussion on the virtues of Surah An-Nisa, highlighting how it advocates for the rights of the oppressed and marginalized, particularly women and orphans. This part of the discussion underscores the Surah’s role in challenging the pre-Islamic practices that demeaned women and deprived orphans of their rights, showcasing the transformative power of its divine guidance.Diving into the core of the article; a thorough analysis of the various themes presented in Surah An-Nisa is conducted. This section meticulously examines the legislative and moral directives concerning the rights of orphans, ensuring they are treated with fairness and compassion. The article elaborates on the Islamic principles governing dowry (Mahr), illustrating how Surah An-Nisa establishes a woman’s right to it as a form of security and respect. The discussion extends to contemporary issues related to dowry, exploring how the teachings of Surah An-Nisa can be applied to address and rectify modern-day challenges surrounding this practice. Furthermore, the article delves into women’s rights, highlighting how Surah An-Nisa was revolutionary in setting forth unprecedented rights for women in areas such as marriage, inheritance, and social conduct. It discusses the Surah’s prohibition of certain types of marriage, the equitable treatment of women, and the establishment of clear guidelines for inheritance, ensuring women are rightful beneficiaries. Additionally, the analysis covers the rights of relatives, emphasizing the importance of maintaining familial bonds and the equitable distribution of wealth among family members. Key Words: Qur’ān, Surah an-Nisā’, Women, Social, Moral, Legal Issues.